PEMBERDAYAAN SDM UNTUK MENINGKATKAN KESEJAHTERAAN EKONOMI MASYARAKAT - Hardiantini, Ela; Erponis, Nuru Kalumidya; Septiani, Yeni (Yayasan Education and Social Center, 2025)
Human resource (HR) empowerment is a crucial step in improving the economic well-being of communities. In the context of community service, the theme